Analisis Fatwa DSN-MUI No: 26/DSN-MUI/III/2002 Terhadap Implementasi Akad Rahn Emas pada Produk Gadai Emas Bank Syariah Indonesia KCP Medan Adam Malik - Adelia Cahyani; Muhammad Zuhirsyan; Hubbul Wathan (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
The growth of the Islamic pawn industry demonstrates a significant contribution in supporting public access to financing, particularly through gold pawn products based on the Rahn contract. Bank Syariah Indonesia (BSI), as the largest Islamic bank in Indonesia, offers this product based on the DSN-MUI Fatwa No. 26/DSN-MUI/III/2002. This study aims to analyze the compliance of the implementation of the gold Rahn contract at BSI KCP Medan Adam Malik with the fatwa and identify substantive obstacles in practice. The study used a qualitative method with a case study approach through interviews, observation, and documentation. Respondents consisted of bank officers, customers, and representatives of the Indonesian Ulema Council (MUI). Data analysis was conducted descriptively qualitatively through reduction, presentation, and drawing conclusions. The results of the study indicate that structurally the implementation of the Rahn contract is in accordance with the fatwa provisions, as reflected in the Gold Pawn Proof Letter (SBGE) containing the Rahn contract, along with transaction details. However, there are substantive gaps. First, some officers misunderstand because they assume that the pawned gold belongs to the bank. Second, the determination of the Ujrah (usury) is based on business strategy and customer segmentation, not the actual storage costs, thus creating the potential for gharar (gharar) and resembling usury (riba). Third, customer education regarding the Ijarah contract is not optimal, particularly regarding the object of Ijarah. In conclusion, the implementation of the Rahn contract at BSI KCP Medan Adam Malik is normatively valid, but faces substantive challenges in terms of transparency, fairness, and understanding of the contract. This study recommends strengthening customer education, increasing staff capacity, and providing substantive oversight by the Sharia Supervisory Board.